Tomato protein phosphatase 2C influences the onset of fruit ripening and fruit glossiness - Liang, Bin (Journal of experimental botany, 2021)
© The Author(s) 2020. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.